Euro Interest Rate Swap Yields: A GARCH Analysis - Tanweer Akram; Khawaja Mamun (International Journal of Empirical Economics, 2025)
This paper models the month-over-month change in euro-denominated (EUR) long-term interest rate swap yields. It shows that the change in the short-term interest rate has an economically and statistically significant effect on the change in EUR swap yields of different maturity tenors in the subsequent period, after controlling for various macroeconomic and financial variables, such as the month-over-month change in inflation or core inflation and the growth of industrial production, and the percentage change in the equity price index, the exchange rate, and the size of the European Central Bank’s (ECB) balance sheet. It uses a generalised autoregressive conditional heteroskedasticity (GARCH) approach to model the dynamics of the monthly change in EUR swap yields and their volatility. The results of the estimated models of EUR swap yields of different maturity tenors extend the Keynesian view that the central bank’s monetary policy actions have a decisive influence on long-term government bond yields and long-term market interest rates, primarily through their effects on the current short-term interest rate.